A SOCIOLINGUISTIC STUDY OF TABOO IN ALAS PURWO BANYUWANGI - YAMANI, AZMI ZAKKI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: sociolinguistic, taboo, folklore, social mental structure Language can be the most powerful attribute to define the mental structure of the people in particular group. Taboo is one of the social phenomena that can be used as an object of the study in sociolinguistic field. Taboo consists of normative rules that are transferred orally through generations without any specific rational. The appeareance of these taboo rules in society are accepted by the society as their local belief in communicating with others. In order to find the relationship between social mental structure and taboo rules, oral tradition as the device to transfer the information must be examined. The oral tradition as the social behaviour that havethe same characteristics with the taboo rules appear as the form of language that can also define the social mental structure. Based on those backgrounds, the writer is interested in analyzing the existence of taboo rules in Banyuwangi society especially in Alas Purwo which is touted as one of the most superstisious society in Banyuwangi area. The focus of the study attempts to find answers of this following problems of study: (1) What kind of taboo are believed in Alas Purwo Banyuwangi, (2) What are the meanings of the taboo in Alas Purwo Banyuwangi, (3) What are the types of folklore for each of the taboo in Alas Purwo? In the study, the writer uses Keith and Burridge (2006) categorization related to thefunction and the impact of breaking the rules. The writer also uses Danandjaja’s (1982) categorization of folklore. The result of the study shows that there are 4 fatal taboos, 1 exploiting taboo, 1Uncleanliness taboo, and 9 less serious taboo. From those taboos, there are two types of folklore that namely Myth and Legend. There are 10 myths and 3 legends in Alas Purwo. This result proves that eventhough the development of technology and information has grown fast in Banyuwangi area, the societ y’s subconscious mind still cannot accept the modernity principles in their life which demands eliminating the traditional beliefs which are full of superstition and myths. The writer suggest the study of taboo in Banyuwangi area be developed by the nextresearcher by tracking the existence of the characters like Werjo and Minak Jinggo with the historical data taken.